Pengaruh Penggunaan Dana Desa dalam Bidang Pembangunan Desa dan Bidang Pemberdayaan Masyarakat Desa terhadap Kemiskinan Desa di Kabupaten Pemalang Tahun 2019-2020 - Sofa Sundarti; Mulyo Hendarto Robertus (Diponegoro Journal of Economics, 2022)
Poverty is a problem faced by all countries. Both developed countries, but the problem of poverty is more common in developing countries. One of the reasons for the problem of poverty in developing countries is that development conditions in developing countries are still unstable. To overcome this, the government implements a fiscal decentralization policy with a village fund program which is expected to be able to reduce poverty. The priorities for using village funds include village development and village community empowerment, for this reason the purpose of this study is to analyze the effect of the realization of village funds used in the field of village development and in the field of village community empowerment in every village in Pemalang Regency in 2019 to 2020. Ssecondary data by using the selected Fixed Effect (FE) method, the dependent variable used in this paper is village poverty and two independent variables, namely the realization of village funds in the field of village development and the realization of village funds in the field of empowerment of rural communities with the research population of all villages in Pemalang Regency. This uses purposive sampling method to determine the sample used in the paper. The results of this indicate that the independent variable simultaneously has no effect on village poverty, while partially the variable realization of village funds in the field of village development has a negative value with a coefficient value of -0.362448 and a probability value of 0.0824 which means the realization of village funds in the field of village development, it has an effect on reducing the amount of village poverty but is not significant, while the realization of village funds in the field of village community empowerment has a partially negative significant effect on rural poverty with a coefficient value of -0.358970 and a probability value of 0.0000 which means that each the addition of 1 million realizations in the field of village community empowerment was able to reduce the number of poor people by 36 people.